2013
DOI: 10.1371/journal.pone.0056425
|View full text |Cite
|
Sign up to set email alerts
|

Month of Birth and Mortality in Sweden: A Nation-Wide Population-Based Cohort Study

Abstract: BackgroundMonth of birth – an indicator for a variety of prenatal and early postnatal exposures – has been associated with life expectancy in adulthood. On the northern hemisphere, people born in the autumn live longer than those born during the spring. Only one study has followed a population longitudinally and no study has investigated the relation between month of birth and mortality risk below 50 years.Methods and resultsIn this nation-wide Swedish study, we included 6,194,745 subjects, using data from pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
3
28
1
Order By: Relevance
“…The indicator was used in demographic studies by Doblhammer and Vaupel (2001), Doblhammer (2004), and Doblhammer et al (2005), who showed that life expectancy is still influenced by the month of birth among people who are currently elderly, but that this influence is becoming smaller over successive cohorts. Ueda et al (2013) confirmed these findings for Sweden in a study exploring the relationship between month of birth and late-life mortality with Swedish population register data. In general, research has shown that people born in the spring have a lower life expectancy than those born in the winter, and that in the southern hemisphere the pattern is shifted by half a year in line with the seasons there.…”
Section: Month Of Birthsupporting
confidence: 75%
See 1 more Smart Citation
“…The indicator was used in demographic studies by Doblhammer and Vaupel (2001), Doblhammer (2004), and Doblhammer et al (2005), who showed that life expectancy is still influenced by the month of birth among people who are currently elderly, but that this influence is becoming smaller over successive cohorts. Ueda et al (2013) confirmed these findings for Sweden in a study exploring the relationship between month of birth and late-life mortality with Swedish population register data. In general, research has shown that people born in the spring have a lower life expectancy than those born in the winter, and that in the southern hemisphere the pattern is shifted by half a year in line with the seasons there.…”
Section: Month Of Birthsupporting
confidence: 75%
“…Meanwhile, the procreational habits hypothesis suggests that couples from different social strata have different preferences for giving birth in a particular season, and that couples might also differ in terms of their seasonal lifestyle. Doblhammer (2004) for Austria and Ueda et al (2013) for Sweden provided evidence that while the spring-born have a lower life expectancy, they also have a higher average educational level. Thus, controlling for socioeconomic status would serve to increase the month-of-birth differences.…”
mentioning
confidence: 99%
“…This is relevant particularly in historical populations in which both nutritional status and the burden of infectious diseases exhibited great seasonal variation. Season of birth can also be an indicator of temperature, sun exposure and vitamin D levels (Flouris et al 2009;Ueda et al 2013). Second, in contrast with birth order or parental age at conception, this indicator is cyclical and largely exogenous; younger or older siblings may or may not be born during the same season and the distribution of births along the seasonal cycle captures variations that are largely unrelated to family background and other socio-economic or environmental conditions (Doblhammer 2004).…”
Section: The Influence Of Seasonality Of Birth On Longevitymentioning
confidence: 99%
“…That is, systematic differences among people born in different months come into existence well before the intervention of the education/training system. In particular, season of birth has been found to be associated with diverse physiological and psychological traits, such as birth weight (Currie andSchwandt 2013, Tanaka et al 2007), adult height (Tanaka et al 2007, Weber, Prossinger andSeidler 1998), life expectancy (Doblhammer and Vaupel 2001, Flouris et al 2009, Lowell and Davis 2010, Ueda et al 2013, and novelty/sensation seeking (Benjamin et al 1996, Ebstein et al 1996, Lesch et al 1996, among others.…”
Section: Literature Reviewmentioning
confidence: 99%